Experimental investigation on wave characteristics due to interference of catamaran demi-hulls in waves - Thi Loan Mai; Anh Khoa Vo; Aeri Cho; Van Thuan Mai; Hyeon Kyu Yoon (International Journal of Naval Architecture and Ocean Engineering)
The presence of twin hulls of a catamaran has a strong impact on wave pattern in the whole inner region due to interference between waves generated by each demi-hull. Consequently, wave profiles as well as wave height become complicated and unpredictable in the inner region not only in still water, but also in the presence of waves. Determining wave characteristics between demi-hulls of the catamaran is essential for predicting the operation of an autonomous underwater vehicle (AUV) throughout the launch and recovery (LAR) process. This study performed an experiment to investigate wave characteristics between demi-hulls of the catamaran under regular and irregular waves at various wave directions and speeds. The experiment was designed to measure wave elevation in the inner region between demi-hulls in waves using ultrasonic sensors and capacitance wave probes. The experimental method and setting were verified exacting by comparing the motion response of the catamaran measured by the Qualisys system with numerical simulation using the 3D panel method. Then, wave elevation in the inner region was measured and analyzed to wave height which is a representative parameter of regular waves and to wave spectral density and significant wave height which are representative parameters for irregular waves. These parameters were compared to those of the ocean waves to understand influences of wavelengths, sea states, wave directions, and speeds on wave characteristics between demi-hulls of the catamaran. Plotting of difference from ocean waves indicated the discrepancy in wave characteristics among positions in the inner region, wavelengths, wave directions, sea states, and speeds compared to ocean waves. Results of wave characteristics in the inner region are valuable to analyze motion response and behavior of AUV during LAR process of unmanned surface vehicle (USV).